ISOLATION, IDENTIFICATION AND ANTIBIOGRAM PATTERN OF AVIBACTERIUM PARAGALLINARUM FROM JAPANESE QUAILS - V. Thenmozhi; S. Malmarugan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A total of 53 trachea, air sacs, lung, and infra orbital sinus exudates were collected from 5 commercially reared Japanese quail farms showing typical symptoms of infectious coryza. Avibacterium paragallinarum was isolated and identified using selective media and by biochemical identification methods. Biochemical identification tests such as satellitism, IMViC tests and carbohydrate fermentation tests were performed. In total, eight A. paragallinarum isolates were isolated and identified from the field samples and the species were confirmed with the species specific PCR, which gives the amplicon size of 500bp. Antibiogram of A. paragallinarum showed 100% resistance for Ampicillin, neomycin, Pefloxacin, co-trimaxazole, furazolidone, streptomycin, Cephalexin and Amikacin with 90% for Gentamycin and 70% for oxytetracycline.